A simple, one-step polychromatic staining method for epoxy-embedded semithin tissue sections. (15th October 2018) - Morikawa, Shunichi; Sato, Azusa; Ezaki, Taichi
Abstract : A simple polychromatic staining method for epoxy-embedded semi-thin tissue sections was developed to allow more informative and convincing histological investigation in various fields of research and education. This technique enabled clear differentiation of various tissue structures according to color tone and intensity, thereby facilitating the detection of fine structural differences. Abstract: Although conventional toluidine blue staining is a common technique used for rapid observation of semithin sections prior to transmission electron microscopy, it is monochromatic and insufficient for accurate identification of different tissue components by light microscopy. Additionally, polychromatic staining methods generally require step-by-step processes involving different dyes, and it is often difficult to balance the color tone of each step. In this study, we developed a simple polychromatic staining method for epoxy-embedded tissue sections. We stained preheated sections with an aqueous ethanol solution of azure B and basic fuchsin, with the addition of sodium tetraborate to enhance the staining efficacy. We optimized various staining conditions to enable sufficient coloration easily and consistently in a single, rapid staining step, using a single staining-mixture solution. Our method enabled clear differentiation of various tissue structures according to color tone and stain intensity, thereby facilitating the detection of fine structural differences, including various organelle and inclusion bodies. This technique represents a simple polychrome-staining method to allow more informative and convincing histological investigation in various fields of research and education.